2022
DOI: 10.3390/jcm11185258
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing and Fracture Mapping in Pelvic and Acetabular Fractures: A Systematic Review and Meta-Analysis

Abstract: Three-dimensional printing and fracture mapping technology is gaining popularity for preoperative planning of fractures. The aim of this meta-analysis is to further understand for the effects of 3D printing and fracture mapping on intraoperative parameters, postoperative complications, and functional recovery on pelvic and acetabular fractures. The PubMed, Embase, Cochrane and Web of Science databases were systematically searched for articles according to established criteria. A total of 17 studies were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Procedures include orthopedic surgery [25, 57–77, 9597]. More precisely foot and ankle fracture fixation [76], tibial plateau fracture surgery [73, 74], open reduction and internal fixation surgery [75, 97], fracture surgery [57, 6065, 69, 71, 72, 74, 95, 96], treatment of pelvic ring injuries [70], osteotomy [58, 66], total hip and knee arthroplasty [67]. Quinones and colleagues mention [77] complex enbloc resections of primary vertebral tumors, complex cran-iocervical junction surgeries, spinal deformity correction surgeries, fracture-dislocations of the thoracic and lumbar spine, minimally invasive surgery, disc replacement surgery.…”
Section: Reviews In Medical 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures include orthopedic surgery [25, 57–77, 9597]. More precisely foot and ankle fracture fixation [76], tibial plateau fracture surgery [73, 74], open reduction and internal fixation surgery [75, 97], fracture surgery [57, 6065, 69, 71, 72, 74, 95, 96], treatment of pelvic ring injuries [70], osteotomy [58, 66], total hip and knee arthroplasty [67]. Quinones and colleagues mention [77] complex enbloc resections of primary vertebral tumors, complex cran-iocervical junction surgeries, spinal deformity correction surgeries, fracture-dislocations of the thoracic and lumbar spine, minimally invasive surgery, disc replacement surgery.…”
Section: Reviews In Medical 3d Printingmentioning
confidence: 99%
“…These authors followed the PRISMA guidelines [1, 3, 57, 9, 1319, 2226, 28, 3037, 3945, 47, 4979, 8192, 94106], were registered [4, 14, 16, 40, 47, 51, 5355, 60, 63, 70, 72, 73, 84, 88, 90, 91, 95, 98, 99] and did a bias assessment [4, 5, 7, 1418, 23, 2931, 33, 3941, 49, 51, 5357, 6062, 65, 67, 69, 71, 72, 7476, 78, 8284, 86, 90, 96, 97, 99, 100].…”
Section: Reviews In Medical 3d Printingmentioning
confidence: 99%
“…As a result of the development of additive manufacturing technology, two-dimensional elements are transformed into three-dimensional conformations and presented as interactive software or printed models, enabling students to fully comprehend the spatial structure of real objects without the use of any material objects ( Abdulcadir et al, 2020 ). Taking into account the complicated anatomy of the pelvis, 3D printed models can guide newcomers in understanding the borders of pelvic tumors, the typology of complex pelvic fractures, etc ( Lee et al, 2022 ; Wu et al, 2022 ). Moreover, physicians can also quickly develop their operating skills while learning via surgical training based on 3D printed models.…”
Section: Hip Joint Diseasementioning
confidence: 99%
“…4 3D-printing and virtual surgery planning have found significant interest in the field of orthopaedics, leading to considerable advancement in preoperative surgical planning. [5][6][7] Indeed, it is found that 3D models allow surgeons to visualize anatomy three-dimensionally and aid in the planning and execution of complex surgeries. [8][9][10] 3D printing of porous structure offers an attractive means to improve the fabrication of bone models and facilitate their understanding for both academic studies and surgical planning.…”
Section: Introductionmentioning
confidence: 99%